Understanding the association between time spent caregiving and well-being among employed adults: testing a model of work–life fit and sense of community. Issue 2 (15th March 2017) - Hilbrecht, Margo; Lero, Donna S.; Schryer, Emily; Mock, Steven E.; Smale, Bryan
ABSTRACT: This study examines factors associated with work–life fit and sense of geographic community as mediators of the negative association between caregiving demands and well-being among employed informal caregivers. Data were drawn from a larger project assessing well-being among residents of three mid-size cities in Ontario, Canada. A subsample was selected of informal caregivers who worked for pay for at least eight hours/week ( n  = 276). Caregiving demands were measured by time spent caring for an adult who was a relative, friend, or neighbour. Well-being followed a holistic conceptualization advanced by the Canadian Index of Wellbeing. The more time spent caregiving, the lower participants' well-being ratings were. This association was mediated by perceived time adequacy, income adequacy, and sense of community, such that the more time participants spent caregiving, the lower their ratings of these three resources. This explained the initial association of caregiving hours with reduced well-being. Enhanced well-being was more strongly associated with sense of community than any other factor, which supports the importance of the community domain in understanding well-being among employed caregivers and suggests its further testing with other population groups. Policy implications for employers and community organizations are provided.